2021
DOI: 10.1053/j.semtcvs.2020.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and Measurement of Aerosolisation in Different Chest Drainage Systems

Abstract: The aim of the study was to assess the degree of aerosolisation in different chest drainage systems according to different air leak volumes, in a simulated environment. This novel simulation model was designed to produce an air leak by passing air through and agitating a fluorescent fluid. The air leak volume and amount of fluorescent fluid were tested in various combinations and aerosolisation was assessed at 10-minute intervals using the ultraviolet light. The following chest drainage systems were compared: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Many thoracic surgical patients have the requirement for intercostal chest drainage which is connected to a drainage system in the immediate postoperative period. A bubbling chest drain with an ambient air exhaust can generate aerosols [55]. The British Thoracic Society suggests mitigating this risk by constant connection of chest drains to wall suction, use of a digital chest drain system, or use of an anti-viral filter attached to a standard chest drainage system [56].…”
Section: Chest Drainagementioning
confidence: 99%
“…Many thoracic surgical patients have the requirement for intercostal chest drainage which is connected to a drainage system in the immediate postoperative period. A bubbling chest drain with an ambient air exhaust can generate aerosols [55]. The British Thoracic Society suggests mitigating this risk by constant connection of chest drains to wall suction, use of a digital chest drain system, or use of an anti-viral filter attached to a standard chest drainage system [56].…”
Section: Chest Drainagementioning
confidence: 99%
“…This is generally supervised by multiple health care professionals such as nurses and physiotherapists and the patient can get in contact with other patients circulating in the ward. The study from Mustaev and coll 1 support the safety practice to organise this activity in a way to prevent the patient to wear a single chamber system while performing physical activity or mobilising in the ward minimising the risk of viral spreading to other patients and health care professionals.…”
mentioning
confidence: 95%
“…The study of Mustaev and coll. 1 contributes to add to the current knowledge about safety of chest drainage systems currently in use in our operative rooms and wards. They were able to demonstrate through a basic laboratory simulation that single chamber systems are at increased risk of generating aerosols in the surrounding atmosphere in the presence of an active air leak.…”
mentioning
confidence: 99%
“…In this original article, Mustaev and colleagues sought to define the degree of aerosolization from chest tube drainage systems in the context of the COVID-19 pandemic. 2 They conceptualized and developed a novel simulation model for measuring aerosol generation by agitating a fluorescent fluid with different air flow rates. The aerosolized particles were measured under ultraviolet light.…”
mentioning
confidence: 99%
“…They concluded that the single chamber chest drainage system is much more likely to generate aerosols than a three-chamber or digital drainage system and therefore, single chambers should not be used in patients with air leak. 2 …”
mentioning
confidence: 99%